2022
DOI: 10.1093/hr/uhac291
|View full text |Cite
|
Sign up to set email alerts
|

RcbHLH59-RcPRs module enhances salinity stress tolerance by balancing Na+/K+ through callose deposition in rose (Rosa chinensis)

Abstract: Basic helix-loop-helix (bHLH) proteins play pivotal roles in plant growth, development, and stress responses. However, the molecular and functional properties of bHLHs have not been fully characterized. In this study, a novel XI subgroup of the bHLH protein gene, RcbHLH59, was isolated and identified in rose (Rosa spp.). This gene was induced by salinity stress in both rose leaves and roots, and functioned as a transactivator. Accordingly, silencing RcbHLH59 affected the antioxidant system, Na+/K+ balance, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 72 publications
0
11
0
Order By: Relevance
“…RcMYB8 improved drought and salt tolerance by influencing ROS dynamic changes and proline accumulation. In addition, previous studies have shown a connection between RcMYB8 and RcPR5/1 (Su et al 2021 ), and RcPR5/1 was proved to enhance salinity resistance in rose (Su et al 2023 ). We next examined the relevant gene expression corresponding to ROS scavenging, proline synthase and pathogenesis-related-5 (PR5) in both RcMYB8 -silenced and RcMYB8 -overexpressing plants.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…RcMYB8 improved drought and salt tolerance by influencing ROS dynamic changes and proline accumulation. In addition, previous studies have shown a connection between RcMYB8 and RcPR5/1 (Su et al 2021 ), and RcPR5/1 was proved to enhance salinity resistance in rose (Su et al 2023 ). We next examined the relevant gene expression corresponding to ROS scavenging, proline synthase and pathogenesis-related-5 (PR5) in both RcMYB8 -silenced and RcMYB8 -overexpressing plants.…”
Section: Resultsmentioning
confidence: 92%
“…Under drought or salinity stresses, plants accumulate some physiological indicators [relative conductivity (REL), Chl content, chlorophyll fluorescence, callose accumulation] to improve their adaptability under these unfavorable conditions (James et al 2018 ; Tang et al 2019 ; Su et al 2023 ). Among them, REL is a vital indicator reflecting the severity of cellular membrane impairment (James et al 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Salt treatment of rose leaves was described previously [ 68 ]. Thirty JDG and 30 DMS rose cuttings with good rooting and uniform appearance were selected, and mature leaves of similar size were collected.…”
Section: Methodsmentioning
confidence: 99%
“…For silencing of RhTSPO , a 400-bp fragment containing a 200-bp 3′ UTR fragment was cloned into pTRV2 using the Xba I and Kpn I restriction sites. Silencing of RhETR3 and RhTSPO in rose plants by VIGS was performed as previously described [ 53 ].…”
Section: Methodsmentioning
confidence: 99%